A case report of sporadic Creutzfeldt-Jakob disease in an Asian origin coronavirus disease-19 patient: An enigma - Suman Choudhary,; Mayank Sonkar,; Ashok Kumar Saxena, (Indian Journal of Case Reports, 2021)
Creutzfeldt-Jakob disease (CJD) is a rare, degenerative, and fatal brain disorder affecting about one in every 1 million persons/year worldwide, with a typical duration from onset to death is only 7 months. In our case report, we describe a patient of Sporadic CJD (sCJD) who presented to the hospital during the coronavirus disease (COVID-19) pandemic and the intensive care unit experience and precautions taken to prevent the iatrogenic spread of the disease. This case was diagnosed following confirmation of all the typical clinical, radiological, and laboratory features of this condition. From all recent data on the pathogenesis of the sub-category of prion disease and the immune responses to severe acute respiratory syndrome coronavirus-2, we can suggest that coronavirus disease can lead to exaggerated and accelerated pathogenesis and manifestations of neurodegenerative disorders such as of our patient’s sCJD. We have tried to highlight the challenges in managing patients with a rare disease such as sCJD and how its progression can be intensified by COVID-19.